Correlation of risk factors and aspect scores in patients with middle cerebral artery ischaemic stroke in HUSM - Eie, Teo Yin (2016)
Purpose: To correlate the GCS and risk factors with ASPECTS among patients with middle cerebral artery territory ischaemic stroke in HUSM. Materials and methods: In an institutional review board-approved study, the authors obtained 148 samples from medical ward of HUSM. Patients with clinically proven stroke and underwent non-contrast enhanced CT brain were recruited. Fasting blood sugar and fasting lipid profiled were obtained. CT brains were reviewed to obtain ASPECTS of each individuals. Correlation and Regression were used to assess the association and prediction between GCS and various risk factors with ASPECTS. Results: We were able to obtain 148 patients whom 140 were Malays, 8 were non-Malays, 48 were male and 100 were female. There was good positive correlation between GCS and ASPECTS (r=0.615, p<0.001). On univariate analysis, only GCS was statistically significant (OR 0.076; 95%CI 0.011 to 0.515, r2 = -2.58, p<0.05). One unit increament in GCS has 92.4% lesser odds to have worse ASPECTS when other confounders were not adjusted. However, multivariate analysis showed none of the variables was statistically significant. Conclusions: We suggested that GCS is associated significantly with ASPECTS and can be applied to predict ASPECTS when other confounders were not added. The risk factors including age, gender, fasting blood sugar, total cholesterol level, triglyceride level, LDL level and HDL level have no correlation with severity of stroke.